CTIM-34. PRELIMINARY SAFETY AND EFFICACY DATA ON TWO PATIENTS WITH RELAPSED/REFRACTORY CNS LYMPHOMA TREATED WITH EMAVUSERTIB (CA-4948) AND IBRUTINIB COMBINATION: A SUBSET ANALYSIS OF TAKEAIM LYMPHOMA TRIAL. (14th November 2022) - Iqbal, Madiha; Tun, Han; Joffe, Erel; Grommes, Christian; Nowakowski, Grzegorz; Lunning, Matthew; Ramchandren, Radhakrishnan; Li, Chia-Cheng; Zhao, Wanying; Martinez, Elizabeth; von Roemeling, Reinhard; Earhart, Robert; et al.
Abstract: BACKGROUND: Emavusertib, an oral interleukin-1 receptor-associated kinase 4 (IRAK4) inhibitor, targets toll-like receptor (TLR) and interleukin-1 receptor (IL-1R) signaling pathway in B-cell proliferation. IRAK4 forms a Myddosome complex with MYD88 adaptor protein and drives overactivation of NF-κB, causing inflammation and tumor growth. Emavusertib has been reported to be well tolerated and active as monotherapy in heavily pretreated relapsed/refractory (R/R) non-Hodgkin lymphoma (NHL). In a murine PDX model of primary CNS lymphoma (PCNSL), emavusertib crossed the blood-brain barrier, resulting in tumor response and prolonged survival. In combination with Bruton tyrosine kinase (BTK) inhibitors, emavusertib showed in vivo anti-cancer synergy in B-cell NHL. METHODS: This is an ongoing open-label trial (NCT03328078) in patients with R/R NHL. Currently, we are in the dose escalation portion of combination therapy to evaluate safety and efficacy following treatment of emavusertib at dose levels of 200 or 300mg BID with ibrutinib at full prescribed dose. As of May 6th, 2022, 13 patients have been treated with emavusertib+ibrutinib combination therapy. RESULTS: Among the 13 patients, two were diagnosed with R/R PCNSL and had several prior lines of anti-cancer therapy. Emavusertib in combination with ibrutinib (560 mg daily) appeared to be well tolerated in these two subjects. One patient experienced Gr3 treatment-related adverse events (thrombocytopenia, muscle weakness, pain). The preliminary efficacy data demonstrated one CR and one SD. The patient who achieved CR after the combination therapy was originally intolerant to high-dose methotrexate based chemoimmunotherapy and did not achieve complete remission after switching to ibrutinib, providing early clinical evidence of CNS penetration and anti-tumor activity of emavusertib. CONCLUSION: In R/R PCNSL, these preliminary data suggest that combination therapy has a tolerable safety profile with promising anti-cancer activity and may overcome ibrutinib resistance.